Sequential treatment with sildenafil and riociguat in patients with persistent or inoperable chronic thromboembolic pulmonary hypertension improves functional class and pulmonary hemodynamics. (15th October 2018) - Darocha, Szymon; Banaszkiewicz, Marta; Pietrasik, Arkadiusz; Piłka, Michał; Florczyk, Michał; Wieteska, Maria; Dobosiewicz, Anna; Szmit, Sebastian; Torbicki, Adam; Kurzyna, Marcin
Abstract: Background: This study evaluated the incremental effect of riociguat on pulmonary hemodynamics in patients with inoperative or persistent chronic thromboembolic pulmonary hypertension (CTEPH) treated previously with sildenafil. Methods: The retrospective study included 28 patients diagnosed with CTEPH who were ineligible for surgical treatment due to distal thrombi location or who suffered from persistent CTEPH after pulmonary endarterectomy and who were treated with sildenafil at a dose of 25 mg TID for a minimum of 3 months. Sildenafil was subsequently discontinued, and riociguat therapy was started with gradually increasing doses. Right heart catheterization was performed and WHO functional class (FC) was assessed in each patient at three time points: before starting sildenafil therapy (baseline), before the transition to riociguat, and after 3 to 6 months of therapy with riociguat. Results: Compared to baseline, the use of sildenafil and riociguat significantly decreased pulmonary vascular resistance (PVR) (10.47 ± 3.56 vs. 7.81 ± 3.58 Wood units, p < 0.001) and mean pulmonary arterial pressure (PAP) (54.1 ± 11.6 vs. 46.1 ± 13.2 mm Hg; p < 0.001) while increasing cardiac output (CO) (4.31 ± 0.88 vs. 4.85 ± 0.87 L/min; p = 0.007). Switching from sildenafil to riociguat reduced PVR by 14% (p = 0.005) and the mean PAP by 6% (p = 0.03) while increasing CO by 11% (p = 0, 002). The number of patients with WHO FC III and IV symptoms decreased from 71, 4% to 57, 1% (p = 0, 02) after the change from sildenafil to riociguat. Conclusions: Replacing sildenafil with riociguat in patients with inoperable or persistent CTEPH may improve pulmonary hemodynamics and FC. Highlights: Riociguat may improve pulmonary hemodynamics in sildenafil-treated CTEPH patients. Replacing sildenafil with riociguat may improve physical functioning. Riociguat may reduce systemic arterial blood pressure and vascular resistance. This may reduce left ventricular afterload in patients with hypertension and HF.